Stimulasi Perkembangan Motorik Anak Autis Melalui Terapi Bermain : Snakers And Ladders Di Sekolah Pendidikan Khusus dan Pendidikan Layanan Khusus Mutiara Bunda Kota Bengkulu - Iskandar, Siska; Indaryani; Sari, Maritta; Sari, Nengke Puspita (Gayaku Publisher, 2024)
Autism or Autism Spectrum Disorder (ASD) is a general neurodevelopmental disorder that is genetic and heterogeneous with underlying cognitive characteristics and usually occurs together with other conditions such as being unable to carry out social interactions and seeming to live in one's own world. One of the problems with autistic children is the behavioral aspect. One effort that nurses can make to overcome motor problems is through play therapy. The community service methods used are socialization and training carried out at the Mutiara Bunda Special Education and Special Service Education School (PK-PLK), Bengkulu City. After carrying out community service activities targeting parents and autistic children with motor development disorders, the results obtained were that there was an increase in parents' knowledge about how to stimulate motor skills in autistic children as well as an increase in motor skills in autistic children. It is hoped that the development of children with special needs, especially autistic children, can develop optimally and can improve the health status of autistic children so that autistic children can become great children in the future.